Global epidemiology, genetic environment, risk factors and therapeutic prospects of mcr genes: A current and emerging update - Mmatli, Masego; Mbelle, Nontombi Marylucy; Osei Sekyere, John (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Mobile colistin resistance (mcr) genes modify Lipid A molecules of the lipopolysaccharide, changing the overall charge of the outer membrane. Results and Discussion: Ten mcr genes have been described to date within eleven Enterobacteriaceae species, with Escherichia coli, Klebsiella pneumoniae, and Salmonella species being the most predominant. They are present worldwide in 72 countries, with animal specimens currently having the highest incidence, due to the use of colistin in poultry for promoting growth and treating intestinal infections. The wide dissemination of mcr from food animals to meat, manure, the environment, and wastewater samples has increased the risk of transmission to humans via foodborne and vector-borne routes. The stability and spread of mcr genes were mediated by mobile genetic elements such as the IncHI2 conjugative plasmid, which is associated with multiple mcr genes and other antibiotic resistance genes. The cost of acquiring mcr is reduced by compensatory adaptation mechanisms. MCR proteins are well conserved structurally and via enzymatic action. Thus, therapeutics found effective against MCR-1 should be tested against the remaining MCR proteins. Conclusion: The dissemination of mcr genes into the clinical setting, is threatening public health by limiting therapeutics options available. Combination therapies are a promising option for managing and treating colistin-resistant Enterobacteriaceae infections whilst reducing the toxic effects of colistin.